Roles of Primary Care Nurses in Participation of Management the District Health System in Community Hospitals, Health Service Networks Region 12 - Khongrueang, Traimas; Boonyoung, Nongnut; Laimek, Sasithorn (Journal of Research in Nursing-Midwifery and Health Sciences, 2020)
This descriptive qualitative research aimed to explore the roles, barriers and problem solving of primary care nurses in participation of the management of District Health System (DHS) in community hospitals, Health Service Networks Region 12. The conceptual framework for this study was the situation specific of the management of the DHS. Informants were 30 primary care nurses responsible for the management of DHS in 10 community hospitals. Data were collected using group interview. Descriptive statistics and content analysis were used to analyze the data. The results showed that the primary care nurses participated in the management of DHS by being 1) a coordinator between healthcare team and the local governing bodies, 2) a leader in working with the community, 3) a motivator to involve people and community to participate in managing the health system, 4) a role model in creating generosity working atmosphere, 5) a supporter of a continuous monitoring the DHS performance, 6) a coach for public health human resource development, and 7) a proactive healthcare provider. The major barriers were the cooperation among healthcare team and others and the misunderstanding that the district health system should only be managed by the public health unit. Assigning responsibility among the healthcare team and the involvement of all stakeholders especially those in the leading positions were implemented. The study results suggest that primary care nurses should strengthen their role as a coordinator and regularly monitor the progression of DHS while anticipating an involvement of local backbones.